2016
DOI: 10.1177/003335491613100116
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Suicide in the Community: Prevalence and Correlates in One U.S. State

Abstract: Exposure to suicide is pervasive and occurs beyond family; as such, it is imperative to identify those with perceived closeness to the decedent. This hidden cohort of suicide-exposed people is at elevated risk for psychopathology and suicidal ideation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
108
3
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 15 publications
3
108
3
3
Order By: Relevance
“…Although some previous studies have asked about respondents’ intentions to assist a person at risk of suicide, this risk has always been overtly expressed, despite most suicide communications being indirect (Shand et al., ; Wasserman et al., ; Wolk‐Wasserman, ). Given the high number of community members exposed to close family members or friends at risk of suicide (Cerel et al., ; Maple et al., ), it is imperative to understand whether community members can recognize indirect signs of suicide risk and respond accordingly. Our findings show that both indirect and direct verbal suicide communications increase the likelihood of community members intending to assist the person at risk in getting professional help, and asking about suicidal thoughts, suggesting some recognition of indirect verbal suicide communications.…”
Section: Discussionmentioning
confidence: 99%
“…Although some previous studies have asked about respondents’ intentions to assist a person at risk of suicide, this risk has always been overtly expressed, despite most suicide communications being indirect (Shand et al., ; Wasserman et al., ; Wolk‐Wasserman, ). Given the high number of community members exposed to close family members or friends at risk of suicide (Cerel et al., ; Maple et al., ), it is imperative to understand whether community members can recognize indirect signs of suicide risk and respond accordingly. Our findings show that both indirect and direct verbal suicide communications increase the likelihood of community members intending to assist the person at risk in getting professional help, and asking about suicidal thoughts, suggesting some recognition of indirect verbal suicide communications.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that for every suicide, 6–10 people are profoundly affected and may be at risk for suicidal behaviors. 28,29 Nearly half of veterans report knowing someone who died by suicide, 30 with 65% of those knowing more than one decedent. 31 Exposure to suicide death (“knowing of,” knowing, or identifying with the person who died by suicide 32 ) has been shown to predict subsequent suicide ideation and attempts in veterans and civilians, 31,33 highlighting the importance of this risk factor among servicemembers.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing random‐digit dial data from a single U.S. state sample of 1,736 adults, we reported that almost half of participants (48.3%) reported lifetime exposure to suicide (Cerel et al., ). Suicide‐exposed individuals were more likely than nonsuicide exposed to report suicide ideation (9.0% vs. 5.3%).…”
mentioning
confidence: 99%